From Stone to Seed: Objects and Counter-memory Activism in Brazil amidst Anticolonial Demonumentalizations - Gomes, Lilian (Politologija, 2024)
This article reflects upon objects and actions of counter-memory activism in Brazil in the wake of anticolonial demonumentalizations. Initially, it focuses on statues symbolizing colonial and traumatic pasts, notably the Borba Gato statue in São Paulo, dedicated to a colonial explorer. The monument was set ablaze in July 2021, sparking widespread debate. The discussion deepens with the commemoration of Marielle Franco, a councilwoman and human rights advocate who was murdered in 2018. The interplay between memory initiatives and political activism is examined, with tributes analyzed as collective authorship by black and feminist movements. Ethnographic data from Rio de Janeiro and digital environments inform this analysis. Events related to monuments and other objects are viewed as political rituals in the struggle against forgetting. Statues, street signs, graffiti, posters, and other forms of counter-memory supports are identified as focal points for understanding the relationship between objects, artistic-political practices, and public life.